Electoral competition as a determinant of fiscal decentralization - Mario Jametti; Marcelin Joanis (Center for Economic Studies and ifo Institute (CESifo), 2011)
Fiscal decentralization is high on the agenda in policy fora. This paper empirically investigates the underlying causes of fiscal decentralization, based on the predictions of a simple political economy model. We argue that the likeliness that a central government engages in devolution of powers depends in important ways on the political forces that it faces, the theory's main insight being that the central government's electoral strength should, all else being equal, decrease that government's share of spending. Consistent with the model's predictions, empirical results from a panel of democracies support the relevance of political factors as determinants of fiscal decentralization. The relationship between central government electoral strength and both expenditure and revenue centralization emerges as negative and non-linear.
Keywords: H77; D72; H11; 330; fiscal decentralization; fiscal federalism; vertical interactions; partial decentralization; elections